The concept of spirit in the structure of Yuri Shevchuk’s worldview - Ivanov, Dmitry; Mikhailovich, Shaklein Victor; Stepanovich, Mamontov Alexander; Stanislavovna, Mikova Svetlana (Opción, 2019)
This paper analyzes the specifics of the conceptual worldview based on the material of the lyrics of famous Russian rock musician and singer Yuri Shevchuk via psycholinguistic, philosophical, linguocultural, and linguo-cognitive approaches. As a result, the concept spirit in the conceptual worldview is not only a key system important component, but primarily serves as a certain cognitive harmonizing stabilizer that balances and ultimately nullifies the negative traits of the Russian national character. As a conclusion, the formation of the conceptual worldview of the rock poet is genetically related to the process of modeling his cognitive-pragmatic program.